2000
DOI: 10.1093/pcp/41.6.684
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Wound-Responsive Genes Identifies an Immediate-Early Expressed Gene Encoding a Highly Charged Protein in Mechanically Wounded Tobacco Plants

Abstract: In order to identify genes that are temporally and spatially regulated during wound response, a cDNA population in mechanically wounded tobacco leaves was screened by the fluorescence differential display method. Of 28 clones initially identified to have altered levels of transcripts within 3 h of wounding, eight were characterized. Although each clone showed a unique pattern of transcript accumulation, one distinct clone was further characterized because of its immediate-early response. Its transcripts began … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
38
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 32 publications
4
38
0
1
Order By: Relevance
“…Isolation of NtDRM1 cDNA-Initially, a DNA fragment encoding NtDRM1 was obtained by differential display of a cDNA population derived from wounded tobacco leaves (18). A full-length 2.4-kb cDNA of NtDRM1 was isolated by colony hybridization of a tobacco (N. tabacum) cDNA library using the NtDRM1 fragment as a probe and sequenced for both strands using a Big Dye terminator sequencing kit (Applied Biosystems, Foster City, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Isolation of NtDRM1 cDNA-Initially, a DNA fragment encoding NtDRM1 was obtained by differential display of a cDNA population derived from wounded tobacco leaves (18). A full-length 2.4-kb cDNA of NtDRM1 was isolated by colony hybridization of a tobacco (N. tabacum) cDNA library using the NtDRM1 fragment as a probe and sequenced for both strands using a Big Dye terminator sequencing kit (Applied Biosystems, Foster City, CA).…”
Section: Methodsmentioning
confidence: 99%
“…The searches revealed a high degree of sequence identity between GmMIPS1 and MIPS genes from plants and other organisms. The highest scoring match was to the tobacco MIPS sequence (Hara et al, 2000), which showed 80.6% identity to GmMIPS1 at the nucleotide level and 92.2% identity at the amino acid. Sequence identity to yeast was 40.2% at the nucleotide level and 41.5% at the amino acid level (Johnson and Henry, 1989), further confirming the high degree of conservation among MIPS sequences from different sources.…”
Section: Isolation and Analysis Of A Mips Cdnamentioning
confidence: 99%
“…A sequence similar to the yeast MIPS gene was identified in Spirodela polyrrhiza, an aquatic angiosperm (Smart and Fleming, 1993). MIPS sequences have been reported from Arabidopsis (Johnson, 1994), Citrus paradisii (Abu-Abied and Holland, 1994), common ice plant (Ishitani et al, 1996), and tobacco (Hara et al, 2000), and are highly conserved at the nucleotide level.…”
mentioning
confidence: 99%
“…Treated leaf samples were harvested at appropriate time points and immediately frozen in liquid nitrogen before further analyses. The fluorescence differential display was performed essentially as described (Hara et al 2000), except that samples were fractionated by agarose gel electrophoresis.…”
mentioning
confidence: 99%